Plasmonic nanoprobes for stimulated emission depletion nanoscopy - Cortés,E; Huidobro,PA; Sinclair,HG; Guldbrand,S; Peveler,WJ; Davies,T; Parrinello,S; Görlitz,F; Dunsby,C; Neil,MAA; Sivan,Y; Parkin,IP; et al. (ACS Nano, 2016)
Plasmonic nanoparticles influence the absorption and emission processes of nearby emitters due to local enhancements of the illuminating radiation and the photonic density of states. Here, we use the plasmon resonance of metal nanoparticles in order to enhance the stimulated depletion of excited molecules for super-resolved nanoscopy. We demonstrate stimulated emission depletion (STED) nanoscopy with gold nanorods with a long axis of only 26 nm and a width of 8 nm. These particles provide an enhancement of up to 50% of the resolution compared to fluorescent-only probes without plasmonic components irradiated with the same depletion power. The nanoparticle-assisted STED probes reported here represent a ∼2 × 103 reduction in probe volume compared to previously used nanoparticles. Finally, we demonstrate their application toward plasmon-assisted STED cellular imaging at low-depletion powers, and we also discuss their current limitations.